Unraveling the Steric Link to Copper Precursor Decomposition: A Multi‐Faceted Study for the Printing of Flexible Electronics (Small Methods 4/2023). Issue 4 (20th April 2023) - Mrig, Shreya; Bhide, Malavika A.; Zhou, Ye; Stanton, Nils; Wang, Jingyan; Douglas, Samuel P.; Tinker, Henry R.; Mears, Kristian L.; Bakewell, Clare M.; Knapp, Caroline E.
Abstract : Inside Back Cover In article number 2300038, Caroline E. Knapp and co‐workers have established a link between the geometry of copper precursors and their decomposition to copper metal by single crystal X‐ray diffraction investigation alongside density functional theory calculations. Precursor synthesis and their decomposition profiles are reported. Inkjet printing yielded conductive ( ρ = 4.7–5.3 × 10 −7 Ω m; ≈30% bulk) copper features onto paper and polyimide substrates at 125 °C and 150 °C.